Nuruddin Ar-Raniry: Kajian Pemikiran Tokoh Muslim Indonesia - Muhammad Fayrus (Budapest International Research and Critics University, 2018)
In the Nusantara archipelago, the process of Islamization began with port cities which were at the same time the royal capital, such as Samuera Pasai and Malacca, which later became the center of the royal palace which became the center of Islamic intellectual development over the official protection of the rulers, followed by the emergence of clerical figures such as Hamzah Fansuri, Samsuddin as-Sumatrani, Nuruddin Ar-Raniry, and Abdur Rauf as-Singkili in the Aceh kingdom. While in Java there is Wali Songo. 2 These great ulamas were credited with spreading Islamic knowledge in Southeast Asia and later established Islamic educational institutions such as dayahs so that a university in Aceh developed.